UPAYA INDONESIA DALAM MEMBERANTAS TERORISME DI ERA SUSILO BAMBANG YUDHOYONO (Pendekatan Tentang Pengeboman di Wilayah Indonesia) - Sumardewi, Luh Ashari (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
ABSTRACK Since the bombings in Indonesia, the term terrorism began widely known by the public. Terrorism is a great enemy to be dealt with either by the government together with the community. Terrorism is a serious problem because the broad impact for society and for the government and the Indonesian State. for the Yudhoyono government made ??several attempts to anticipate and eradicate acts of terrorism in Indonesia. Keywords : terrorism, bombs, Indonesia, Susilo Bambang Yudhoyono